Effect of delayed application of cyhalofop-butyl on the removal of Chinese sprangletop (Leptochloa chinensis (L.) Nees) in rice paddy fields in the southern part of the Okayama Prefecture - Kato-Noguchi, Hisashi; Akazawa, Masahiro (Journal of Weed Science and Technology, 2023)
We investigated the effect of dose and timing of application of a cyhalofop-butyl emulsion (CB agent) on the growth of Chinese sprangletop (Leptochloa chinensis (L.) Nees), a weed species that invades rice paddy fields by spreading through its stolons. The application of 300–900 g a.i./ha of CB agent before heading showed an increase in efficacy with increasing dosage. At 900 g a.i./ha application, a significant suppression was observed in the growth and panicle booting of this species. The weed height and number of panicles reduced from 14% to 28% and 0% to 1%, respectively, 55–63 days after treatment when compared to the untreated control. The effect of the same chemical dose varied with the time of treatment. The pre-emergence treatment was found to be the most effective in suppressing panicle emergence. In contrast, the effect of treatment after the beginning of panicle emergence decreased, and the number of panicles in the middle of panicle emergence was about the same as that in the untreated control.